The defendant in the shadows: investigative strategy or violation of the right to defense? - Ventura Granados, Fátima Milagros (2024)
This article examines the practice of the Public Prosecutor's Office whereby a person against whom a material accusation is directed is unjustifiably not formally included in the investigation under the belief of avoiding possible obstruction to its purposes, while conducting diligences aimed at gathering evidence that would determine their responsibility. The aim is to question the legitimacy of this practice and analyze possible solutions, assessing their compatibility with the constitutional rights of the accused, especially their right to defense. An exhaustive analysis of procedural criminal regulation, case law, and related doctrine concerning this practice is conducted. It is concluded that the "shadow accused" is not a legitimate investigative strategy but rather a practice that violates the rights of the accused, emphasizing the importance of rights protection as a means to halt this violation and ensure greater protection of the accused's rights in the criminal process.